Preparing bioactive surface of polystyrene with hydrophobin for trypsin immobilization. (13th May 2016) - Niu, Baolong; Li, Bingzhang; Wang, Huifang; Guo, Ruijie; Liang, HaiXia; Qiao, Mingqiang; Li, Wenfeng
Abstract: A simple and reliable enzyme immobilization technique which can retain their catalytic activity for a long time is interest in many technologies. Here, the trypsin was immobilized by physisorption on polystyrene (PS) surface coated with a class I hydrophobin recombinant HGFI (rHGFI). X-ray photoelectron spectroscopy and water-contact-angle measurements demonstrated that the hydrophobicity of the PS could be well improved by rHGFI modification, and the self-assembled rHGFI showed an admirable stability on the hydrophobic PS surface against hot SDS rinsing. The enzyme activity assay illustrated that the capacity of rHGFI could enable it to well intermediate trypsin on PS surface and allow its immobilization lasting in an active form. The results obtained in this work show a way that surface modification with rHGFI should be an easy and feasible strategy for applications of enzyme-based catalytic surfaces in biosensing.